2001
DOI: 10.1097/00004424-200105000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Motion During the Cardiac Cycle and Optimal ECG Triggering for Coronary Artery Imaging

Abstract: For coronary artery screening, the optimal ECG trigger time should be determined according to the patient's heart rate, thus greatly reducing motion and motion artifacts during 100-ms acquisitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
98
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 24 publications
9
98
1
1
Order By: Relevance
“…Previous studies have shown that reducing average heart rate and heart rate variability is beneficial for reducing cardiac imaging artifacts (1,2). Despite these findings, little quantitative information is available about how heart rate and heart rate variation if affected by a cardiac CT scan acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that reducing average heart rate and heart rate variability is beneficial for reducing cardiac imaging artifacts (1,2). Despite these findings, little quantitative information is available about how heart rate and heart rate variation if affected by a cardiac CT scan acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Under the breath-holding condition, the greatest amount of coronary motion occurred in the right coronary artery (RCA), followed by the left circumflex (LCX), left main (LM), and left anterior descending (LAD) arteries, as also found in Ref. 16. The respiratory motion adds another global translation to the heart position.…”
Section: Coronary Motion Analysismentioning
confidence: 66%
“…Different coronary arterial segments have relatively complex motion patterns during the cardiac cycle (45)(46)(47). Accurate slice registration between the slice with the reinverted magnetization and the imaged slice is mandatory and may be compromised due to cardiac motion.…”
Section: Discussionmentioning
confidence: 99%